The Analysis of the Juvenile Delinquency Trigger Factors and the Handling Efforts - Sulthon Sulthon; Muhammad Misbahul Munir (Proceedings Series on Social Sciences & Humanities, 2023)
Transitional period development emerges significant changes in psychological aspects. These changes often lead to values and norms conflict. Juvenile delinquency is caused by unresolved conflicts in childhood during the transitional period. This study aims to: 1) determine the factors that trigger juvenile delinquency; 2) discover juvenile delinquency solution, 3) find out the inhibiting factors for tackling juvenile delinquency. This research uses literature analysis with the data from related literature as analytical material. Data analysis uses descriptive qualitative and exploratory analysis. The results showed, 1) there are internal and external trigger factors for juvenile delinquency; 2) Efforts to overcome the occurrence of juvenile delinquency are through parenting and attention to adolescents, including psycho-education; 3) Inhibiting factors in efforts to overcome juvenile delinquency such as negative peer influence, uncontrolled use of social media, lack of parental attention, and permissive attitude. This research provides information about the juvenile delinquency cause and prevention.